Selfies no Tinder masculinidades como performance - Dutra, Flora Ardenghi (2017)
The present research explores how self-promotion promotes new masculinities in cyberspace presented in the world's most popular relationship application, Tinder, and how these men relate to the smartphone to manage male performances from self-image. It seeks to understand how gender and subjectivities build the self from a shared habitus among men and how these identities can be perceived by the image in the construction of a profile in a mobile device application. Through a multisituated ethnography, 590 correspondents and ten users who collaborated with the research from August 2015 to March 2017 were analyzed. In the methodological discussion, the multisituated ethnography seeks to account for subjectivities from a socio-anthropological perspective. The study is a contribution to the field of masculinities and gender identities crossed by the online network. The research conveys to the Social Sciences, especially in the anthropological current of the cyberculture. The analysis was structured in order to understand how masculinities act in selfies, that is, how gender reproductions can be understood by users of the Tinder application.